2014
DOI: 10.1007/s00449-014-1315-1
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of orange peel, a food industrial waste, in the production of exo-polygalacturonase by pellet forming Aspergillus sojae

Abstract: The production of exo-polygalacturonase (exo-PG) from orange peel (OP), a food industrial waste, using Aspergillus sojae was studied in submerged culture. A simple, low-cost, industrially significant medium formulation, composed of only OP and (NH 4 ) 2 SO 4 (AS) was developed. At an inoculum size of 2.8 9 10 3 spores/mL, growth was in the form of pellets, which provided better mixing of the culture broth and higher exo-PG activity. These pellets were successfully used as an inoculum for bioreactors and 173.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Comparing PGase activity achieved in the present study with the values reported in the literature in submerged fermentations, yields were clearly improved with respect to those previously obtained with A. sojae . PGase activity obtained when A. sojae was grown in shake flasks with maltrin as the main CES was nearly 17 U/ml .…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Comparing PGase activity achieved in the present study with the values reported in the literature in submerged fermentations, yields were clearly improved with respect to those previously obtained with A. sojae . PGase activity obtained when A. sojae was grown in shake flasks with maltrin as the main CES was nearly 17 U/ml .…”
Section: Resultssupporting
confidence: 73%
“…In another study, a pre‐optimized culture medium containing orange peel and sugar beet syrup was tested in a 5‐L bioreactor, resulting 145 U/ml of PGase activity . Fed‐batch cultivation of A. sojae in 5‐L bioreactors using orange peel as CES further enhanced the PGase activity levels to 244 U/ml . Hence, utilization of apricot pomace combined with orange peel in submerged cultures allowed at least a 1.5‐fold increase in PGase activity from A. sojae with respect to previous works.…”
Section: Resultsmentioning
confidence: 68%
“…The inflection point in the DOT trend, consistent with the above explanation, has been reported previously for A. sojae growing in submerged cultures utilizing other by-products such as orange peels and apricot pomace. 7,8 In this type of submerged fermentation with filamentous fungi where powdered, vegetable raw material is used as carbon source, oxygen limitation has proved to be a factor that affects enzyme yields significantly. For instance, by preventing the DOT from dropping below 20% a 1.5-fold improvement in PG yields was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, industrial production of pectinases is mainly performed by A. niger , partly due to the high titers obtained, although great efficiency in the production of extracellular enzymes is not a hallmark restricted to this species. In fact, within recent years several studies have been performed that report the effective production of PGs by A. sojae …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation